2022
DOI: 10.1002/jia2.25961
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world use and outcomes of dolutegravir‐containing antiretroviral therapy in HIV and tuberculosis co‐infection: a site survey and cohort study in sub‐Saharan Africa

Abstract: Introduction Dolutegravir is being scaled up globally as part of antiretroviral therapy (ART), but for people with HIV and tuberculosis co‐infection, its use is complicated by a drug–drug interaction with rifampicin requiring an additional daily dose of dolutegravir. This represents a disadvantage over efavirenz, which does not have a major drug–drug interaction with rifampicin. We sought to describe HIV clinic practices for prescribing concomitant dolutegravir and rifampicin, and characterize vir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…ART programs in several countries, including Brazil, shifted from using non-nucleoside analog reverse transcriptase inhibitors, such as EFV, to INI during the period in which the cohort was formed. INIs have superior efficacy, greater tolerability, and a high genetic barrier [ 26 ]. However, concerns arose about the compromise in the therapeutic response of these drugs due to the drug–drug interaction of INI with rifampicin, requiring an increase in the dose in coinfected patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ART programs in several countries, including Brazil, shifted from using non-nucleoside analog reverse transcriptase inhibitors, such as EFV, to INI during the period in which the cohort was formed. INIs have superior efficacy, greater tolerability, and a high genetic barrier [ 26 ]. However, concerns arose about the compromise in the therapeutic response of these drugs due to the drug–drug interaction of INI with rifampicin, requiring an increase in the dose in coinfected patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns arose about the compromise in the therapeutic response of these drugs due to the drug–drug interaction of INI with rifampicin, requiring an increase in the dose in coinfected patients. Despite this disadvantage vis-à-vis EFV and the greater complexity of the treatment regimen, real-world studies have shown that dolutegravir does not negatively impact viral suppression [ 26 ]. Another study that evaluated raltegravir in coinfection indicated that the use of the medication twice a day compromises adherence and, consequently, the effectiveness of the treatment, but the alternative use of this medication is recommended [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This interaction risk could potentially be exacerbated by escalating RIF dosages [ 155 ]. In another study conducted in coinfected HIV and TB patients undergoing treatment, it was evidenced that the decrease in serum concentrations of dolutegravir led to an adjustment of the daily drug dose to maintain its effectiveness in addition to increasing the risk of hepatic toxicity [ 156 ].…”
Section: Limitations Of Conventional Therapies In Tb Treatmentmentioning
confidence: 99%